Peran Pendidikan Kesehatan Sekolah Dalam Meningkatkan Kesadaran Remaja Terhadap Bahaya Narkoba - Rahmat Pannyiwi; Akhwan Ali (Asosiasi Guru dan Dosen Seluruh Indonesia, 2026)
Drug abuse among adolescents is a public health problem that can negatively impact physical, psychological, and social development, as well as academic achievement. Low knowledge and lack of understanding regarding the risks of drug use are factors that increase adolescents' vulnerability to substance abuse. School health education is an important promotive and preventive strategy to raise adolescents' awareness of the dangers of drugs. This study aims to determine the role of school health education in raising adolescents' awareness of the dangers of drugs. This study used a quantitative approach with a pre-experimental, one-group pretest-posttest design. The sample size was 60 students selected using purposive sampling. The research instrument used a questionnaire to assess adolescents' knowledge and awareness of the dangers of drugs. The intervention was implemented through health education in the form of counseling, discussions, and educational media. Data analysis was performed using a paired sample t-test. The results showed an increase in students' knowledge and awareness after receiving school health education. There was a significant difference between the levels of knowledge before and after education (p < 0.05). School health education is effective in raising adolescents' awareness of the dangers of drugs and can be used to prevent drug abuse in the school environment.